The incidence of corporate tax in the manufacturing sector of Ghana. - Agyei, Baah Samuel (KNUST, 2025)
A Thesis Submitted In Partial Fulfilment Of The Requirements For The Degree Of Master Of Business Administration (Accounting- Option).